On the distribution and status of Carcharodus lavatherae, Pyrgus carthami, and P. serratulae (Lepidoptera: Hesperiidae) in Slovenia - Rudi Verovnik (Natura Sloveniae)
A detailed survey of the publications and main Slovenian collections showed that only limited information on the distribution of Carcharodus lavatherae, Pyrgus carthami, and Pyrgus serratulae is available. Within the framework of the Slovenian butterfly atlas survey, several additional records have been gathered during the past two decades. C. lavatherae was found in four separate areas, but the knowledge about its threat status and habitat preference is still insufficient due to the scarcity of the encounters. The distribution of Pyrgus carthami in Slovenia is much more limited than considered by previous authors. All confirmed records are confined to southwest Slovenia, where the main strongholds are the south facing slopes north of the Vipava valley and western part of the Kras plateau. The large number of unpublished records is somewhat masking the actual decline of the species in Slovenia. P. serratulae is the most enigmatic of the three species with numerous published records but no vouchers that could verify its presence in Slovenia. The discovery of the species in the Poček military area is the first confirmed observation in Slovenia, putting this species right to the top of the conservation priorities in butterflies.